Effect of deviation from stoichiometry on transport and mechanical properties of Bi2Se3 polycrystals - Menshikova, S. I.; Rogacheva, E. I. (AIP Publishing, 2021)
The dependences of electrical conductivity, the Hall coefficient, the Seebeck coefficient, thermoelectric power factor and microhardness of Bi2Se3 polycrystals on the degree of deviation from stoichiometry 59.9–60.0 at. % Se and temperature (77–300 K) were obtained. The samples exhibited n-type conductivity in the studied ranges of compositions and temperatures. The boundaries of the Bi2Se3 homogeneity region were estimated. A non-monotonic behavior of the concentration dependences of the properties in the studied composition range, associated with a change in the phase composition and defect structure under the deviation from stoichiometry, was observed. The calculation of the power coefficient in the temperature dependence of electron mobility showed that in a stoichiometric Bi2Se3, electrons are predominantly scattered by acoustic phonons, and under the deviation from stoichiometry the contribution of impurity scattering increases. Based on the experimental data, the Fermi energy EF was calculated in the approximation of the relaxation time and within the framework of the single-band model with a quadratic dispersion law. The obtained values of EF showed that both in stoichiometric and non- stoichiometric Bi2Se3, the conduction is mainly due to electrons in the lower conduction subband.
Keywords: mechanical properties; transport properties; critical phenomena; effect of deviation; stoichiometry; Bi2Se3; polycrystals